Experimental and statistical analysis for surface modification of steel and cast iron using Nd:yag laser - Fazliana, Fauzun (2015)
This thesis presents experimental study on laser surface modification of steel and cast iron to enhance surface properties. The aim of this study is to produce laser surface modified layer on AISI H13 tool steel, AISI 1025 low carbon steel and gray cast iron surface with enhance properties for die casting application. An Nd:YAG laser system with pulse processing mode was used to modify AISI 1025 low carbon steel, AISI H13 tool steel and gray cast iron samples. AISI 1025 low carbon steel was processed at four different parameters settings of average power, pulse repetition frequency (PRF), pulse width and scanning speed. AISI H13 tool steel and gray cast iron were processed using 33 full factorial design of experiment (DOE). The full factorial DOE, was designed using three factors namely peak power, PRF and scanning speed at three levels. The factors level for H13 were peak power ranged from 1.7 to 2.5 kW, PRF of 40 to 60 Hz and scanning speed of 1000 to 1400 mm/min. For cast iron, peak power ranged from 0.83 to 1.25 kW, PRF of 50 to 70 Hz and scanning speed of 1000 to 1400 mm/min. The as-received and laser modified surface was characterised for surface morphology, metallographic study, surface roughness and hardness properties. In metallographic study, samples were analysed for laser modified layer depth, focal position effect on modified layer depth and grain size. Results were analysed statistically using ANOVA. Optimisation of processing parameters for H13 tool steel and gray cast iron samples was conducted using Response Surface Method (RSM). A thermal stability test was conducted for H13 tool steel sample with the highest hardness properties at temperature range of 550 to 800 oC. From the findings, the laser modified surface depth in AISI 1025 low carbon steel, AISI H13 tool steel and gray cast iron samples ranged between 50.23 and 455.07 μm, 42.22 and 420.12 μm, and 67.97 and 157.69 μm respectively. Hardness for AISI 1025 was ranged from 255 to 460 HV0.1 while hardness of AISI H13 tool steel modified layer ranged from 1000 to 1427 HV0.1. Hardness of gray cast iron ranged from 250 to 450 HV0.1. The minimum roughness, Ra, achieved in modified H13 was 1.10 μm, while in AISI 1025 and gray cast iron was 8.51 and 3.20 um. From thermal stability test, hardness of laser modified surface reduced to 512.8 HV0.1 after heated at 800 oC. Statistical analysis shows significant quadratic and 2FI models produced for AISI H13 and gray cast iron samples responses. Optimization of DOE for H13 tool steel samples for minimum surface roughness and maximize hardness and modified depth properties resulted in 15 solutions. Optimisation for gray cast iron samples also was set into similar condition like H13 which resulted in 26 solutions. Limitation of temperature in applications can be determined from thermal stability test. At 800 oC, the hardness of laser modified layer found to be dropped 60 % which lower compared to previous works. These findings are significant to enhance surface properties of steel and cast iron for dies and high wear resistant applications